The Formal method of Component Basic Programming - Grischenko, V.N. (Інститут програмних систем НАН України, 2015)
The approach to construction of formal models of component programming, as bases of component theory creation, is offered. The models of components, component environments and external and internal component algebra are considered. The various aspects of these models and their relations with practice of programming are analysed.